Plant flour-based protein hydrolysates enhance table grape tolerance to Botrytis cinerea - Asia Mostacci; Lucia Ferron; Gian Luca Sala; Ornella Incerti; Antonio Ippolito; Simona Marianna Sanzani (Journal of Plant Pathology, 2026)
Protein hydrolysates (PHs) are emerging as sustainable biostimulants capable of enhancing plant tolerance to biotic and abiotic stresses. In this study, PHs were produced in-house from soybean and pea flours through enzymatic hydrolysis using two proteolytic enzymes, alcalase and papain, yielding four hydrolysates (PH1–PH4). The resulting PHs were characterized in terms of protein content, degree of hydrolysis, and peptide composition. The efficacy of the PHs in protecting table grape berries against Botrytis cinerea , the causal agent of grey mould, was then evaluated on two cultivars, Red Globe and Italia. The soybean hydrolysate obtained with alcalase (PH1), applied at 3.2 mg/mL, was the most effective treatment in both cultivars, reducing disease incidence by up to 90% compared with untreated controls, with Red Globe showing the greatest responsiveness. In parallel, in vitro assays demonstrated that hydrolysates did not inhibit conidial germination, and only PH2 and PH4 exerted a limited formulation-specific reduction in mycelial growth; overall, these results suggested that their protective effect was largely mediated through indirect mechanisms associated with plant defence responses. Although further large-scale trials are needed, these findings indicate that flour-derived protein hydrolysates represent a promising, low-cost, and environmentally sustainable strategy for enhancing table grape resistance to B. cinerea and reducing reliance on synthetic plant protection products.

Biocontrol potential of Bacillus velezensis against Fusarium foot rot in durum wheat: insights from in vitro and in vivo trials - Vito Campanella; Asia Mostacci; Claudio Mandalà; Pasquale De Vita; Rosa Petralia; Ornella Incerti; Antonio Ippolito; Simona Marianna Sanzani (European Journal of Plant Pathology, 2026)

First report of pseudopithomyces mori causing leaf spot on mandarin in Italy - Ornella Incerti; Mario Masiello; Marika Desopo; Nancy Terlizzi; Rosalba Latrofa; Asia Mostacci; Lucia Convertini; Paola Ferrante; Antonio Ippolito; Simona Marianna Sanzani (Journal of Plant Pathology, 2024)